2015
DOI: 10.1021/acs.langmuir.5b00288
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Adsorption-Induced Initial Depinning Behavior in Evaporating Water and Nanofluid Sessile Droplets

Abstract: A surfactant-induced autophobic effect has been observed to initiate an intense depinning behavior at the initial stage of evaporation in both pure water and nanofluid sessile droplets. The cationic surfactant adsorbing to the negatively charged silicon wafer makes the solid surface more hydrophobic. The autophobing-induced depinning behavior, leading to an enlarged contact angle and a shortened base diameter, takes place only when the surfactant concentration is below its critical micelle concentration (cmc).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Other chemicals such as FeSO 4 .7H 2 O were provided from Merck (Germany) and all other chemicals were of analytical grade. Typical properties of SDS and MWCNTs are listed in Table 1.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other chemicals such as FeSO 4 .7H 2 O were provided from Merck (Germany) and all other chemicals were of analytical grade. Typical properties of SDS and MWCNTs are listed in Table 1.…”
Section: Chemicalsmentioning
confidence: 99%
“…Due to the extensive use of surfactants in today's world, they can be found in a wide range of daily products such as soaps, detergents, pharmaceutical products, personal care products, as well as in industries including high-technology equipment, painting, and leather products. Hence, the release of these kinds of contaminants to aqueous solutions is inevitable (3,4). According to the ionic characteristics, surfactants are divided into several types including: anionic, cationic, amphoteric, and nonionic.…”
Section: Introductionmentioning
confidence: 99%
“…Other setups, in which vertical plates are soaked in bulk solutions, are also used 9, 2426 . The solutes dissolved in a droplet also affect the drying pattern 27 . It may be possible to design micro-patterns with novel optical and electronic properties by utilizing the interplay between the properties of the solutes and the formed pattern.…”
Section: Introductionmentioning
confidence: 99%
“…4.10 (a)). The velocity for either CTAB or HTAB on glasses increased monotonously The entire retraction of the droplet can be controlled either by autophobing, evaporation, or both [162]. The role of each mechanism can be evaluated by comparing their characteristic time scales as reported by Qu, et al [161].…”
Section: Autophobic Behavior Of Pure Dropletsmentioning
confidence: 97%
“…Limited by the weak mobility of the surfactant molecules across the bare solid surface, the autophobing was widely reported to be irrelevant to the surfactant concentration at a low value for such configuration[101]. For sessile droplets, however, the mechanisms responsible for the dependence of droplet dewetting on surfactant still remain debated, such as the critical concentration of surfactant for the cessation of autophobic effect and the correlation between the contact line retreat and the surfactant concentration[17,18,157,162]. Takenaka, et al[160] demonstrated that the droplet dewetting exhibited a monotonous dependence on surfactant below the critical micelle concentration (cmc), while which is inconsistent with the findings of Frank and Garoff[101] that the contact line retreat is irrelevant to the surfactant inventory below 0.45cmc.…”
mentioning
confidence: 99%